2009
DOI: 10.1093/rheumatology/kep046
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoid-like granulomatosis in patients treated with tumor necrosis factor blockers: 10 cases

Abstract: Sarcoid-like granulomatosis is rare but not exceptional in patients treated with TNF blockers (approximately 1/2800) and does not seem to be related to gender, rheumatic disease or in our series the type of anti-TNF drug used (monoclonal antibodies or soluble receptor). Discontinuation of anti-TNF usually leads to recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
158
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(166 citation statements)
references
References 29 publications
5
158
0
3
Order By: Relevance
“…2 Diagnosis is based on clinical presentation and histopathological findings. 3 Tumor necrosis factor is produced by inflammatory cells such as macrophages, keratinocytes, and T helper 1 (Th1) lymphocytes. 4 It is implicated in the pathogenesis of granulomatous inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Diagnosis is based on clinical presentation and histopathological findings. 3 Tumor necrosis factor is produced by inflammatory cells such as macrophages, keratinocytes, and T helper 1 (Th1) lymphocytes. 4 It is implicated in the pathogenesis of granulomatous inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There is a positive correlation between TNF-α levels and sarcoidotic disease activity. 3,4 Thus, sarcoidosis would be effectively treated with TNF-α blockers. However, cases of cutaneous, pulmonary, and ocular sarcoidosis due to an unexpected and paradoxical effect of these medications have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daien et al estimated the frequency of this adverse event to be at least 0.04% (1/2800). 1 A study published last year found 28 cases, including 16 cases with etanercept, 8 cases under infliximab, and 4 with adalimumab. 2 The median delay between anti-TNFα agent introduction and granulomatosis diagnosis was 19 (range 1-60) months.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent literature review found 28 cases of proved granulomatosis in patients receiving anti-TNFα, 4 of whom had ocular involvement (including 3 cases with etanercept and 1 with infliximab). 2 Herein, we describe a patient with rheumatoid arthritis (RA) who developed chronic bilateral panuveitis and cutaneous nodule on the face, 5 years after administration of adalimumab.…”
mentioning
confidence: 99%